Penggunaan Media Benda Asli untuk Meningkatkan Prestasi Belajar Matematika Siswa SD - Ida Soelastri (JURNAL PEDAGOGIK PENDIDIKAN DASAR, 2022)
During mathematics learning, the real world is only used as a place to apply concepts. Students have difficulty learning mathematics in class. As a result, students do not appreciate or understand mathematical concepts and have difficulty applying mathematics in everyday life. This study aims to determine how the use of real object media can improve student achievement in learning mathematics in elementary school. The method used is a qualitative method with a Class Action Research (CAR) design. The instruments used include observation sheets, tests, questionnaires and attitude scales. Based on the research and discussion results, it can be concluded that the improvement of student achievement in Mathematics subject on the subject of spatial construction through the use of Original Objects media.